Abordagem metodológica e conceitual da economia circular à luz da ciência, tecnologia e sociedade: um panorama da produção científica - Melo, Leticia de Paula Bueno de (2023)
The Circular Economy is an economic and productive model, which differs from the current model by valuing the protection and restoration of natural capital, in order to stimulate renewable flows and manage finite resources, maintaining goods and inputs with a high level of utility and economic value for as long as possible. Academic research has exactly the Circular Economy as strategic for sustainable development, both in the sense of understanding and evaluating strategies already in practice, as well as in the sense of developing scientific yield for new propositions. Thus, this work seeks to analyze – in the light of Science, Technology and Society – how the world stage of research aimed at the Circular Economy is structured, regarding the amplitudes of the methodological and conceptual approaches adopted, as well as, regarding the research institutions and authors of prominence. This research is of an applied nature, with an exploratory and descriptive objective, the approach used is wrong and applies dialectical and inductive scientific methods. To achieve the proposed objective, documental research is used as a technical procedure, whose instruments used are bibliometric survey and content analysis. The understanding of the way in which the Research Field focused on the Circular Economy is structured was achieved through the survey and analysis of quantitative and qualitative data, with the help of Vosviwer and Pajek software. Based on the collected data, we were able to identify prominent authors, institutions and geographic regions in this scenario, as well as research approach trends in the field of CE. It was also understood, based on quantitative and qualitative analyses, that the research bias associated with methodological amplitudes is implicitly related to the social context of its incorporation, in a scenario of influence in both directions.